2021
DOI: 10.1093/nar/gkaa1261
|View full text |Cite
|
Sign up to set email alerts
|

tRNA 3′ shortening by LCCR4 as a response to stress in Trypanosoma brucei

Abstract: Sensing of environmental cues is crucial for cell survival. To adapt to changes in their surroundings cells need to tightly control the repertoire of genes expressed at any time. Regulation of translation is key, especially in organisms in which transcription is hardly controlled, like Trypanosoma brucei. In this study, we describe the shortening of the bulk of the cellular tRNAs during stress at the expense of the conserved 3′ CCA-tail. This tRNA shortening is specific for nutritional stress and renders tRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Whilst the relative affinities of EF-Tu for Balon and aminoacyl tRNA are unknown, the observation of EF-Tu bound to Balon in our cryo-EM maps implies that they are at least somewhat comparable. Various stress and starvation conditions are known to decrease the availability of aminoacylated tRNAs, which are the primary binding partners of EF-Tu [70][71][72] . Therefore, it is plausible that, under these conditions, greater amounts of free EF-Tu would become available for association with Balon, facilitating its delivery to ribosomes.…”
Section: Ef-tu As a Factor Of Stress Responsementioning
confidence: 99%
“…Whilst the relative affinities of EF-Tu for Balon and aminoacyl tRNA are unknown, the observation of EF-Tu bound to Balon in our cryo-EM maps implies that they are at least somewhat comparable. Various stress and starvation conditions are known to decrease the availability of aminoacylated tRNAs, which are the primary binding partners of EF-Tu [70][71][72] . Therefore, it is plausible that, under these conditions, greater amounts of free EF-Tu would become available for association with Balon, facilitating its delivery to ribosomes.…”
Section: Ef-tu As a Factor Of Stress Responsementioning
confidence: 99%
“…As tRNAs are the mediator of protein translation, it is not surprising that a common stress response is the alteration of the cellular tRNA pools. tRNA 3’ end trimming is a known mechanism in Trypanosoma brucei , by which the organism makes tRNAs unable to perform the translation in response to stress [ 89 ]. In humans, tRNA fragmentation can be caused by oxidative stress [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Processing of CCA-termini of tRNAs is well-known mechanism for tRNA quality control in E. coli [reviewed in ( Wellner et al, 2018 )]. In addition, it has been recently reported that CCA-termini of tRNAs are shortened under nutritional stress in Trypanosoma brucei ( Cristodero et al, 2021 ). Under stress condition, tRNAs are trimmed by nuclease LCCR4 resulting in translational repression, and repaired quickly once normal condition is restored ( Cristodero et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been recently reported that CCA-termini of tRNAs are shortened under nutritional stress in Trypanosoma brucei ( Cristodero et al, 2021 ). Under stress condition, tRNAs are trimmed by nuclease LCCR4 resulting in translational repression, and repaired quickly once normal condition is restored ( Cristodero et al, 2021 ). However, whether such mechanisms exist in human cells is still unclear because the data concerning ANG-mediated CCA-cleavage are based largely on in vitro experiments ( Czech et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%